MyUniKLRunner : The Development for UniKL e-Delivery System - Hasbullah, Siti Salwa Bt; Napiah, Nur Azzyati Bt Mahamad (International Journal of Psychosocial Rehabilitation, 2020)
Online food-delivery platforms are expanding largely with bigger choices and convenience throughout all user nowadays. This process taken by allowing the user to easily orders from a wide array of restaurants with a single tap of their mobile phone or any other machines. The business of delivering from any restaurant food to the home is rapidly change as new online platforms to capture the new digital online delivery food markets directly to the users across the world. Furthermore, this current trend also happens in University area, that contribute for fast delivery, especially for the staff and students. For instance, in UniKL MIIT, for every semester, students normally conducted an event or any fund-raising event by selling foods or products in the university area. Thus, by having this research, students and staffs will easily take part by automatically process the request using this proposed MyUniKLRunner system. This research is focusing on how to manage the interaction between buyer and runner on how to buy and deliver the food and services in the area of UniKL MIIT City Campus. This system will help the staff and students that running much time on their task and work to easily cut their time to buy food or services when there has a runner to help on fulfilling their request. In order to get and effective business delivery process, this system went through an extensive testing and evaluation with various types of data. From the test that been conducted, every output and result of the system was successfully verified. In conclusion, this proposed MyUniKLRunner system had been successfully developed where it allows the user (staff and students) and the runner to automatically helping each other in the online delivery process to meet the current trend in online food and service delivery system.